Optimal mix of climate-related energy in global electricity systems. (November 2020) - Chu, Cheng-Ta; Hawkes, Adam D.
Abstract: Existing studies on high renewable share electricity systems are usually based on least cost optimization. Running the related models can be time-consuming when space-time resolution is high. This study investigates the optimal mix of climate-related energies for most countries in the world with optimization models based on three criteria: cost, residual load variability, and portfolio output variability. The objectives of minimizing residual load variability and portfolio output variability are to ensure the overall complementarity of the generation portfolio, which may result in less conventional dispatchable units needed in a system. Compromise solutions based on the three objectives are proposed as the optimal mix. This method can produce solutions in acceptable modelling time, and considers the portfolio output characteristics which can make higher climate-related energy penetration more practical. The results show that the compromise solutions can effectively minimize the three objective values in most countries. The results also suggest that wind power is crucial in higher renewable share systems while solar power does not reach over 50% capacity share. Highlights: A novel multi-objectives optimization model is proposed. The model incorporates residual load variability and portfolio output variability. Power output covariance matrices are calculated at country level. The optimal climate-related energy mix of most countries is proposed. The proposed optimal mix can effectively minimize the objectives.